Light and Plastid Signals Regulate Different Sets of Genes in the Albino Mutant Pap7-1 . Issue 3 (21st September 2017) - Grübler, Björn; Merendino, Livia; Twardziok, Sven O.; Mininno, Morgane; Allorent, Guillaume; Chevalier, Fabien; Liebers, Monique; Blanvillain, Robert; Mayer, Klaus F. X.; Lerbs-Mache, Silva; Ravanel, Stéphane; Pfannschmidt, Thomas
Abstract : The albino pap7 - 1 mutant of Arabidopsis reveals the relative impact of light and plastid developmental stage on the expression of nuclear genes involved in metabolism and photosynthesis. Abstract: Plants possessing dysfunctional plastids due to defects in pigment biosynthesis or translation are known to repress photosynthesis-associated nuclear genes via retrograde signals from the disturbed organelles toward the nucleus. These signals are thought to be essential for proper biogenesis and function of the plastid. Mutants lacking plastid-encoded RNA polymerase-associated proteins (PAPs) display a genetic arrest in eoplast-chloroplast transition leading to an albino phenotype in the light. Retrograde signaling in these mutants, therefore, could be expected to be similar as under conditions inducing plastid dysfunction. To answer this question, we performed plastome- and genomewide array analyses in the pap7 - 1 mutant of Arabidopsis ( Arabidopsis thaliana ). In parallel, we determined the potential overlap with light-regulated expression networks. To this end, we performed a comparative expression profiling approach using light- and dark-grown wild-type plants as relative control for the expression profiles obtained from light-grown pap7 - 1 mutants. Our data indicate a specific impact of retrograde signals on metabolism-related genes in pap7 - 1 mutants reflecting the starvation situation of the albino seedlings. In contrast, light regulation of PhANGs and other nuclear gene groups appears to be fully functional in this mutant, indicating that a block in chloroplast biogenesis per se does not repress expression of them as suggested by earlier studies. Only genes for light harvesting complex proteins displayed a significant repression indicating an exclusive retrograde impact on this gene family. Our results indicate that chloroplasts and arrested plastids each emit specific signals that control different target gene modules both in positive and negative manner.